Morphometric and histochemical study of the human vocal muscle - Guida, Heraldo Lorena [UNESP]; Zorzetto, Neivo Luiz (SAGE Publications, 2000)
The present study was conducted on vocal muscles removed at autopsy from adult individuals (10 men and 8 women, ages ranging from 48 to 78 years) with no laryngeal disease. Histologic analysis was performed with hematoxylin and eosin staining, and histochemical analysis was performed by nicotinamide- adenine-dinucleotide tetrazolium reductase, succinate dehydrogenase, and acid and alkaline myofibrillar adenosine triphosphatase reactions. The histochemical reactions showed that the muscle consists of slow-twitch oxidative (SO), fast-twitch glycolytic (FG), and fast-twitch glycolytic oxidative (FOG) fibers distributed in mosaic form. The frequencies of SO, FOG, and FG fibers were 40.50%, 54.75%, and 4.75%, respectively. The higher frequency of SO and FOG oxidative fibers characterizes the muscle as having aerobic metabolism, resistance to fatigue, and fast contraction. The mean minimum diameters were 31.37 μm for SO fibers and 36.46 μm for FOG and FG fibers.
Keywords: Human; Larynx; Morphology; Vocal muscle